The effect of pH control on synthesis of Sr doped barium titanate nanopowder by oxalate precipitation method. Issue 2 (1st February 2018) - Eun Jeon, Jae; Han, HyukSu; Ryeol Park, Kyeong; Hong, Yu-Rim; Bo Shim, Kwang; Mhin, Sungwook
Abstract: Sr substituted BaTiO3 (BST) nanopowders were prepared using oxalate co-precipitation methods. During synthesis, oxygen was applied to the oxalate solution in order to control the oxidation states of Ti. Control of pH in the solution results in different crystalline phases of the powders after calcination; pure perovskite BST was obtained in the powder prepared at pH 3 solution, while perovskite BaTiO3 (BTO) and impurities were observed in powders prepared at pH 1 solution. Phase transformation from amorphous to crystalline BST during heat treatment was discussed by different analysis technique. Also, morphology and elemental distribution of the pure BST was investigated.